2003
DOI: 10.1080/10903120390937085
|View full text |Cite
|
Sign up to set email alerts
|

M Anagement of the v Iolent P Atient

Abstract: Emergency medical services (EMS) providers must often manage violent or combative patients. The data regarding violence against EMS personnel are poor, but according to studies conducted thus far, between 0.8% and 5.0% of incidents to which EMS personnel respond involve violence or the threat of violence. Physical or chemical restraint is usually the only option available to emergency care providers to control violent patients. Physical restraint, however, can lead to sudden death in otherwise healthy patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 24 publications
0
50
0
1
Order By: Relevance
“…Studies have suggested that between 0.8% and 5.0% of all incidents to which EMS personnel respond involve violence or the threat of violence. 31 The frequency of assault directed against EMS personnel in our study was much higher (27%) because we sampled only restrained patients. There were still few injuries (12/271; 4%) and all were minor (2 required medical treatment, none resulted in lost work).…”
Section: Discussionmentioning
confidence: 82%
“…Studies have suggested that between 0.8% and 5.0% of all incidents to which EMS personnel respond involve violence or the threat of violence. 31 The frequency of assault directed against EMS personnel in our study was much higher (27%) because we sampled only restrained patients. There were still few injuries (12/271; 4%) and all were minor (2 required medical treatment, none resulted in lost work).…”
Section: Discussionmentioning
confidence: 82%
“…Prehospital use of sedatives and antipsychotics, which may be of benefit in patients with ExDS, is increasing but has not been prospectively studied. 1,6,8,9 Other care recommendations that may improve survival include a focus on minimizing the amount of and time in restrictive restraint while still ensuring that field personnel remain safe and early mobilization of advanced life support practitioners. Perhaps most importantly, education for both law enforcement officers and emergency medical services personnel, as occurs in our system, may help protect both patients and providers.…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57][58][59][60] Since the ECD causes moderate muscle contractions it is natural to consider the possibility that an ECD application might exacerbate this acidosis. Animal studies with unventilated anesthetized swine do report pH changes.…”
Section: Acidosis and Rhabdomyolysismentioning
confidence: 99%